The Influence of Work Discipline, Total Quality Management (TQM), and Punishment on Employee Performance at PT. Yuto Packaging Technology Indonesia - Rismawati Rismawati; Tri Mulyani Kartini; Miftakul Huda; Nasrun Baldah; Nadia Nursweta (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence of work discipline, Total Quality Management (TQM), and punishment on employee performance at PT. Yuto Packaging Technology Indonesia. Human resources constitute a critical factor in organizational success, as humans serve as the primary driving force in achieving organizational goals even as technology continues to advance. Employee performance is an important indicator in assessing organizational success and must be supported by factors such as work discipline, TQM, and punishment. This research employed a quantitative approach involving 86 respondents who are employees of the company. Data were collected through a questionnaire designed with a Likert scale to measure the research variables. Data analysis was conducted using SPSS version 25, encompassing validity and reliability tests to ensure the quality of the research instruments. Multicollinearity tests were also performed to examine the existence of relationships among independent variables. To test the hypotheses, multiple linear regression, t-tests, and the coefficient of determination (R²) were used to determine the contribution of independent variables to the dependent variable. The results indicate that work discipline, TQM, and punishment each partially and simultaneously exert a positive and significant influence on employee performance. The model explains 64.2% of the variance in employee performance, indicating that the three variables substantially contribute to performance improvement at PT. Yuto Packaging Technology Indonesia.